Recent progress in perovskite solar cells - khalaji assadi, M (el sevier, 2017)
Perovskite hybrid solar cells are in vogue in solar cell research. Dye-sensitized solar (DSS) cells, thin film solar cell and silicon solar cell, among others, owing to their efficiencies that are comparable to crystalline Si solar cells and ease of fabrication by a low-temperature solution technique. Although perovskite solar cells have been accounted for to exhibit enhanced output of about 21% from about 9.7%, limited researches have been conducted to find out their low stability that impedes outdoor applications. The issue of degradation of perovskite and the stability of perovskite solar cells should be addressed for good reproducibility and long life time with high conversion efficiencies. The present review aims to represent an account of the advancement in the organic, inorganic perovskite solar cells and the extent of fabrication techniques with a view to understand the material efficiency relationships.